Evaluating the availability of nutrients for maintenance and growth in ruminants - K. Gross; D. Harmon; T. Avery (Kansas Agricultural Experiment Station Research Reports, 1988)
Two experiments were performed with mature wether lambs to evaluate availability of selected nutrients and volatile fatty acids for maintenance and growth. We used a technique in which known amounts of volatile fatty acids were infused into the rumen and casein into the abomasum. Sampling portal blood allowed measurement of nutrients absorbed across the gastrointestinal tract. Approximately 49, 62, and 21% of the infused acetate, propionate, and butyrate, respectively, were absorbed across the gastrointestinal tract.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Ruminants; Growth; Maintenance